Reflections of Patriarchy Ideology in the Achievements and Challenges Faced by Women Migrants in Town (Global Journal of Human-Social Science, 2016)
Women migrants do find themselves at the advanced stages in their struggle to combat life in town Such stages are what they recognize as achievements to them However as women they do also face challenges Looking at women achievements and challenges with a gender lens requires narrowing the inquiry on how patriarchy ideology can influences the two This work serves to explain how patriarchy ideology determines what rural-urban women migrants regards as achievement the challenges they face and efforts they make to release themselves from such challenges In-depth interview was conducted among the Gogo rural-urban women migrants in both Dodoma town and Dar es Salaam city This aimed at enhancing the respondents to build up their life stories as regards their experiences within patriarchy system in their areas of origin the way they negotiated through it and how it influenced their integration process in destination areas It was found out that for women migrants acquiring whatever they missed within patriarchy system in rural areas is an achievement for them However women migrants are still surrounded by patriarchy system in town which becomes sources of challenges in their integration process in town Moreover the patriarchy ideology among women and the society at large in town do affect they way women fight against challenges the face This implies that patriarchy ideology has got its roots in every place where men are be it in rural areas or in town In order to eliminate its intended negative impact over women much effort has to be directed toward educating men on the need of gender equality in society for their benefit and the society at large Women will hardly find their right within a strong patriarchy system wherever they are
Keywords: recognize as achievements; face challenges; regards as achievement